2006
DOI: 10.1002/jor.20162
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate prevents femoral periprosthetic bone loss following total hip arthroplasty: Prospective randomized double-blind study

Abstract: Following total hip arthroplasty (THA), femoral periprosthetic bone undergoes a remodeling process that results in bone loss in its proximal regions that may compromise the long-term outcome of THA. Periprosthetic bone loss mainly occurs during the first postoperative months. The question is whether a postoperative treatment with alendronate is effective in reducing periprosthetic bone loss and which doses and duration of treatment are required. In a 12-month prospective, randomized double-blind study, 51 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 16 publications
2
38
0
8
Order By: Relevance
“…Bisphosphonates have been evaluated with regard to prevention of bone loss surrounding THA implants in multiple studies [1,2,12,15,16,37,38]. The ability to help prevent bone loss surrounding THA implants suggests a clinically relevant tool for prevention of osteolysis and stress shielding around these devices and, ultimately, implant failure and revision surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bisphosphonates have been evaluated with regard to prevention of bone loss surrounding THA implants in multiple studies [1,2,12,15,16,37,38]. The ability to help prevent bone loss surrounding THA implants suggests a clinically relevant tool for prevention of osteolysis and stress shielding around these devices and, ultimately, implant failure and revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate quantity or quality of the supporting bone can contribute to THA failure, including aseptic loosening and periprosthetic fracture [27,28]. Multiple studies have evaluated the effect of bisphosphonate use on bone mineral density (BMD) surrounding THA devices [1,2,5,12,15,16,29,32,37,38]. All the studies focused on the short-term effect of a single antiosteoporotic agent on the BMD surrounding the implant.…”
Section: Introductionmentioning
confidence: 99%
“…его способ-ность снижать интенсивность резорбции костной ткани убе-дительно доказана в клинической практике при лечении вы-сокооборотных форм системного остеопороза [8]. имеются также сообщения о его использовании у пациентов после операции эндопротезирования [5,6,23]. однако целесообраз-ность их применения в этих случаях по-прежнему воспри-нимается неоднозначно и есть данные [20], что алендронат не снижает интенсивности остеолиза вблизи компонентов эндопротеза.…”
Section: Discussionunclassified
“…[30] With various numbers of enrolled subjects and different hip implants, other groups have definitely shown that an early treatment of bisphosphonate works well in preventing bone loss. [23,24,30,31,32,33] Those studies strongly suggest that oral bisphosphonate treatment may be one of the effective therapeutic options to improve bone strength in patients at an early administration following THA. They cannot however conclude effectiveness in the late administration following THA.…”
Section: Discussionmentioning
confidence: 99%